The Influence of Transformational Leadership on Employee Performance is Mediated by Work Motivation in CV. Bali Barong - I Made Angga Arimbawa; I Gusti Bagus Honor Satrya (CV. Ulil Albab Corp, 2025)
The decline in the effectiveness of employee performance in organizations has increased organizational awareness, especially management, of the importance of the overall level of employee performance. This awareness is the basis for organizational management to consider factors that can realize employee performance in a sustainable manner, including transformational leadership roles and internal and external motivation of employees. Provide an understanding of transformational leadership formation to employee performance and assess the role of motivation moderation as a research objective. A quantitative approach was used in the study using the analysis of the path analysis method, the data collection method was carried out by distributing questionnaires involving 46 respondents directly from CV Bali Barong employees using the smallest square. This study reveals that the three variable relationships directly have a strong impact between transformational leadership on performance, transformational leadership on work motivation and work motivation on performance. Furthermore, this study shows that there is an influence of motivation mediating between transformational leadership on performance. This finding is one of the references for business leaders, especially the gadget industry, to optimize employee performance and encourage the realization of internal and external organizational motivation through the role of leadership.